2019
DOI: 10.33094/26410265.2019.13.37.45
|View full text |Cite
|
Sign up to set email alerts
|

Progressivity and the Re-Ranking Effect of Healthcare Financing in South East Nigeria

Abstract: This study adopts the Lerman and Yitzhaki approach to measure progressivity and re-ranking effects in health care financing in South East Nigeria. Result supports the existence of regressive healthcare payments. Households that spend more to healthcare financing are unable to maintain their original social status due to net income declining below prepayment income. This could certainly be catastrophic as it takes a huge proportion of the household's income, leaving households with insignificant amount on other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Findings from empirical literature indicate that OOP spending on health generally induced a pro-rich redistribution both in developed and developing countries with vertical inequity dominating. It also generated horizontal inequity and reranking in most of the studies (Bilger, 2008;Ataguba and Mclntyre, 2012;Onyema et al, 2019). Studies also indicated that the REs of the SHI contribution depended on the following factors; level of enrollment, contributory rate and the nature of the scheme.…”
Section: Review Of Theoretical and Empirical Issuesmentioning
confidence: 97%
See 1 more Smart Citation
“…Findings from empirical literature indicate that OOP spending on health generally induced a pro-rich redistribution both in developed and developing countries with vertical inequity dominating. It also generated horizontal inequity and reranking in most of the studies (Bilger, 2008;Ataguba and Mclntyre, 2012;Onyema et al, 2019). Studies also indicated that the REs of the SHI contribution depended on the following factors; level of enrollment, contributory rate and the nature of the scheme.…”
Section: Review Of Theoretical and Empirical Issuesmentioning
confidence: 97%
“…Studies in Nigeria on the income redistributive effects (REs) of health care payments, Ichoku and Fonta (2006), Ichoku et al (2010Ichoku et al ( , 2011 and Onyema et al (2019) have only examined the income RE of the OOP health care payment. The available nationally representative study on the RE of health care funding for Nigeria (Ichoku et al, 2011) employed the Lerman-Yitzhaki Framework, which captured only the vertical and reranking components of redistribution but the issue of horizontal inequity was not addressed.…”
Section: Introductionmentioning
confidence: 99%